Evaluation of the Implementation of the Elderly Posyandu in the Petumbukan Health Center Work Area Deli Serdang District in 2024 - Apriliani, Ade; Ritonga, Ahmad Hafizullah; Ginting, Darmanto (JURNAL KESMAS DAN GIZI (JKG), 2024)
Posyandu was formed to facilitate the elderly in obtaining health services, coaching and developing potential abilities in order to realize an independent person. Monitoring and evaluation of the implementation of Posyandu Petumbukan is important to do by providing education and socialization of the interests of the elderly, facilitating transportation of Posyandu for the elderly that are difficult to reach, taking a personal and empathetic approach by inviting participation, including home visits, providing additional services such as specialist health checks, social activities, and welfare programs. This qualitative study aims to evaluate the implementation of Posyandu in the Petumbukan Health Center Work Area. The informants were 15 people by conducting in-depth interviews equipped with a voice recorder. The research variables were communication, human resources, attitudes, and SOPs. The results of the study were that there was a need for communication training for cadres and health workers to improve the delivery of clearer and more detailed health information, cadres and health workers need to manage queues well, a friendly attitude needs to be maintained and improved with better training, increasing the number of cadres and health workers with special training for elderly health, the health center also needs to ensure the availability of drug and vitamin stocks periodically through better inventory management,